Climate Variability Patterns and Their Ecological Effects on Ecosystems in the Northwestern North Pacific - Ma, Shuyang; Tian, Yongjun; Li, Jianchao; Yu, Haiqing; Cheng, Jiahua; Sun, Peng; Fu, Caihong; Liu, Yang; Watanabe, Yoshiro (Frontiers in Marine Science, 2020)
Climate-induced ecosystem variability is increasingly concerning in recent years. Integrated researches in the northeastern North Pacific have proved the ecological importance of the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO) and El Niño-Southern Oscillation (ENSO) to ecosystem variability. While in the northwestern North Pacific, researches have been independent of each other over different regional ecosystems, and identified relatively weak linkages between these climatic indices (e.g. PDO, NPGO, and ENSO) and variations in the regional ecosystems. Such disassociated researches with unidentified important climate variability patterns may have hampered a holistic understanding of climate-induced ecosystem variability in the northwestern North Pacific. Furthermore, non-stationarity in climate-biology relationships has been proven to be important for ecosystems in the northeastern North Pacific but has not yet been studied in the northwestern North Pacific. Therefore, this research compiles biological, environmental and climatic data in ecosystems in the northwestern North Pacific and employs a suite of analytical techniques, aiming to provide a holistic understanding of the climate-induced ecosystem variability. It shows that ecosystems in the northwestern North Pacific had a leading regime shift in the late 1980s in response to climate variability. The Siberian High, Arctic Oscillation and East Asian Monsoon exhibit greater ecological importance to ecosystem variability than the PDO, NPGO and ENSO. Their variations contribute greatly to sea surface temperature changes and thus variations in ecosystems. Furthermore, modified models considering non-stationary relationships achieve better performances than stationary models, suggesting the existence of non-stationarity in climate-biology relationships in the northwestern North Pacific. This non-stationarity resulted from the decline in variance of the sea level pressure in Siberian High rather than the Aleutian Low as suggested by previous studies in the northeastern North Pacific. Our research provides an improved understanding of the climate-induced ecosystem variability in the northwestern North Pacific, offering implications for furthering research on the entire North Pacific.